2007
DOI: 10.4049/jimmunol.178.10.6596
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant gp120 Vaccine-Induced Antibodies Inhibit Clinical Strains of HIV-1 in the Presence of Fc Receptor-Bearing Effector Cells and Correlate Inversely with HIV Infection Rate

Abstract: Nonneutralizing Abs may play a role in protecting animals and humans from lentiviral infections. We explored the Ab-dependent, cell-mediated virus inhibition (ADCVI) Ab response to recombinant gp120 (rgp120) vaccination in sera from 530 participants in the Vax 004 trial. Serum ADCVI activity was measured against a clinical R5 strain of HIV-1 using peripheral blood mononuclear effector cells from healthy donors. The level of vaccine-induced ADCVI activity correlated inversely with the rate of acquiring HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
159
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 47 publications
7
159
0
Order By: Relevance
“…In the second study, ADCC activity of breast milk IgG correlated with decreased maternal-child transmission of HIV-1 (24). Taken together with an earlier study showing an inverse relationship between ADCVI and HIV-1 acquisition in a subset of Vax-004 subjects (22), substantial data in humans now indicate that Fc-mediated effector functions play a role in reducing HIV-1 acquisition. Our studies shed light on the range of epitopes that are potential targets of potent Fc-mediated effector responses and should aid in further refinements of HIV-1 vaccine candidates.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the second study, ADCC activity of breast milk IgG correlated with decreased maternal-child transmission of HIV-1 (24). Taken together with an earlier study showing an inverse relationship between ADCVI and HIV-1 acquisition in a subset of Vax-004 subjects (22), substantial data in humans now indicate that Fc-mediated effector functions play a role in reducing HIV-1 acquisition. Our studies shed light on the range of epitopes that are potential targets of potent Fc-mediated effector responses and should aid in further refinements of HIV-1 vaccine candidates.…”
Section: Discussionsupporting
confidence: 51%
“…First, studies in HIV-1-infected people (8)(9)(10)(11)(12)(13)(14) and in macaques infected with simian immunodeficiency virus (15,16) consistently show an inverse correlation between Fc-mediated effector functions, including antibody-dependent cell-mediated cytotoxicity (ADCC) (8,9) or antibody-dependent cell-mediated viral inhibition (ADCVI), and viral loads or decreased disease progression (17). Second, vaccine-elicited protection both in nonhuman primates (18)(19)(20)(21) and in a subset of human subjects in the Vax-004 trial (22) correlates with Fc-mediated effector function often observed in the absence of detectable neutralizing antibodies (18)(19)(20)(21). Similarly, there was an inverse relationship between acquisition of HIV-1 and ADCC in the RV144 trial for a subset of subjects who had low to moderate IgA anti-gp120 titers (23).…”
mentioning
confidence: 99%
“…Also in macaques, reduction of SHIV viremia correlated with the Ab-dependent cellular cytotoxicity (ADCC) activity of Abs elicited by an adenovirus-based vaccine (2). In humans, vaccination with recombinant gp120 resulted in an ADCVI response for which magnitude correlated with a reduced rate of sexually acquired HIV infection during the Vax004 trial (3). Thus, an effective HIV vaccine, as well as effective immunotherapy, may depend not only on interactions between Ab and Ag, but also on interactions between FcgRs and their Fc ligands.…”
mentioning
confidence: 96%
“…This assay was used to show that ADCC Abs correlate with protection of monkeys from SIV challenge (12). Forthal and colleagues have recently used convincing assays of in vitro viral replication inhibition to illustrate the effectiveness of HIVand SIV-specific ADCC responses (4,(13)(14)(15).…”
mentioning
confidence: 99%